Efficacy of a Dynamic Armrest for Heavy Joystick Controlled Heavy Vechicles: Could The Same Approach Be Used for Joystick Controlled Wheelchairs? - Murphy, Taylor; Oliver, Michele (CMBES Proceedings, 2007)
No Abstract